2009
DOI: 10.1074/jbc.m109.037960
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Function of Heparan Sulfate in the Regulation of Cell-Cell Fusion

Abstract: Despite the important contribution of cell-cell fusion in the development and physiology of eukaryotes, little is known about the mechanisms that regulate this process. Our study shows that glycosaminoglycans and more specifically heparan sulfate (HS) expressed on the cell surface and extracellular matrix may act as negative regulator of cell-cell fusion. Using herpes simplex virus type-1 as a tool to enhance cell-cell fusion, we demonstrate that the absence of HS expression on the cell surface results in a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 87 publications
(86 reference statements)
0
36
0
Order By: Relevance
“…A third glycoprotein, gD, specifically recognizes 3-OS HS, and this interaction can facilitate fusion pore formation during viral entry (6,7,13). Despite the known importance of HS and 3-OS HS during HSV-1 infection in vitro (14,15), not much is known about their significance during an actual infection in vivo.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A third glycoprotein, gD, specifically recognizes 3-OS HS, and this interaction can facilitate fusion pore formation during viral entry (6,7,13). Despite the known importance of HS and 3-OS HS during HSV-1 infection in vitro (14,15), not much is known about their significance during an actual infection in vivo.…”
mentioning
confidence: 99%
“…The parent HS chain, which contains repeating glucosamine and hexuronic acid dimers, can be 100 -150 residues long and may contain multiple structural modifications. Most common among them is the addition of sulfate groups at various positions within the chain, which leads to the generation of specific motifs, making HS highly attractive for microbial adherence (4,14,15). Emerging evidence suggests that the role of HS in viral infection goes well beyond a role as a low specificity pre-attachment site.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some rare modifications in HS can create an HSV-1 gD receptor (31). It is also involved in negatively regulating virus-induced cell-to-cell fusion and mediating HSV movement along plasma membrane protrusions, a process that is termed surfing (30,32). Moreover, HS has been shown to serve as coreceptor for many viruses, including human immunodeficiency virus (HIV), human cytomegalovirus (HCMV), and varicella-zoster virus (VZV) (13,14,20,44).…”
mentioning
confidence: 99%
“…A recent study also suggested that GAGs have a general role in many cell-cell fusion events (20). We therefore aimed to address the potential role of cell surface GAGs, particularly heparan sulfates, in the FGFRL1-mediated cell fusion process in more detail.…”
Section: Volume 285 • Number 48 • November 26 2010mentioning
confidence: 99%